Analysis of apoptosis related genes in nurses exposed to anti-neoplastic drugs - Maral Ramazani; Razieh Pourahmad Jaktaji; Farshad H. Shirazi; Maria Tavakoli-Ardakani; Ahmad Salimi; Jalal Pourahmad (BMC, 2019)
Abstract Background Anti-neoplastic agents are widely used in the treatment of cancer and some non-neoplastic diseases. These drugs have been proved to be carcinogens, teratogens, and mutagens. Concern exists regarding the possible dangers of the staff handling anti-cancer drugs. The long-term exposure of nurses to anti-neoplastic drugs is still a controversial issue. The purpose of this study was to monitor cellular toxicity parameters and gene expression in nurses who work in chemotherapy wards and compare them to nurses who work in other wards. Methods To analyze the apoptosis-related genes overexpression and cytotoxicity effects, peripheral blood lymphocytes obtained from oncology nurses and the control group. The results Significant alterations in four analyzed apoptosis-related genes were observed in oncology nurses. In most individual samples being excavated, Bcl-2 overexpression is superior to that of Bax. Prominent P53 and Hif-1α up-regulation were observed in oncology nurses. Moreover, all cytotoxicity parameters (cell viability, ROS formation, MMP collapse, Lysosomal membrane damage, Lipid peroxidation, Caspase 3 activity and Apoptosis phenotype) in exposed oncology nurses were significantly (p < 0.001) higher than those of unexposed control nurses. Up-regulation of three analyzed apoptosis-related genes were observed in nurses occupationally exposed to anti-cancer drugs. Conclusion Our data show that oxidative stress and mitochondrial toxicity induced by anti-neoplastic drugs lead to overexpression of apoptosis-related genes in oncology nurses.